Critical Analysis of Charakokta Mahakashaya in the Management of Respiratory System Disorders w.s.r. Covid-19 Pandemic (International Journal of Ayurveda and Pharma Research, 2023)
The World Health Organization (WHO) declared the outbreak a Public Health Emergency of International Concern on January 30, 2020. There is currently no specific drug or targeted intervention available, and current therapy consists solely of symptomatic treatment and supportive care. Objective: The goals of this theoretical research, which grew out of this literature review, were to critically review Charakokta Mahakashaya in the management of respiratory system disorders w.s.r. COVID-19 pandemic and interpret its significance in the modern era. Methodology: The present work is primarily based on theoretical research using related research articles, standard textbooks of epidemiology and classical treatises of Ayurveda. Discussion: The COVID-19 pandemic has posed several challenges to the Indian healthcare system. In Ayurveda, the concept of epidemic was well defined under the heading of Janapadodhwansa. It has been discovered that deaths in COVID-19 were caused by a lack of immunity. The Rasayana drug, which provides passive immunity based on Ojas, antagonises the strength of disorders and prevents them. The AYUSH ministry has issued numerous guidelines regarding COVID-19 potential treatment, which must be statistically studied. Along with combating the current situation, objective assessment of the scientific plausibility of botanical interventions for prevention and treatment is critical, and the world's scientific minds are expected to begin planning strategies for the future as well. Conclusion: To combat this pandemic, the prophylactic and therapeutic potential of traditional and complementary medicine systems such as Ayurveda and Yoga can be demonstrated as effective COVID-19 prophylaxis and adjuvant therapy.